Tata Kelola Potensi Pariwisata Berbasis Kearifan Lokal: Studi Kasus di Dermaga Kereng Bangkirai - Intan Kumalasari; Hugo Peter Clayton Ginting; Tagoan Alvaro Setianu (Public Service and Governance Journal, 2025)
Kereng Bangkirai Pier is one of the leading tourist destinations in Palangka Raya City. However, the potential of local wisdom-based tourism has not been optimally manifested, primarily due to governance issues in the management of the site. This research aims to analyze the governance of tourism potential based on local wisdom in Kereng Bangkirai pier of Palangka Raya City. This research uses a qualitative type with a case study approach. Data collection techniques through observation, interviews, and documentation studies in Kereng Bangkirai pier Palangka Raya City. The data analyzed using narrative analysis guided by the 3A concept—Attraction, Accessibility, and Amenities—proposed by Holloway et al. (2009), to map the local-wisdom-based tourism potential. The findings indicate that the Kereng Bangkirai tourism area meets various indicators within the 3A framework. However, these potentials still require further development to enhance tourist interest. Additionally, the study applied Democratic Governance theory by Norris (2012) as an analytical framework, focusing on four indicators: participation, transparency, accountability, and responsiveness. The results reveal that governance performance in these areas remains suboptimal. The implications of this study highlight the importance of local community involvement in the planning, management, and policy-making processes related to tourism at Kereng Bangkirai Pier. This research is expected to contribute to the development of a tourism governance model that aligns with the needs and aspirations of the local community.